Experimental study on flue gas purifying of MSW incineration using in-pipe jet adsorption techniques - Zhong, Zhaoping (Waste management (New York, N.Y.), 2008)
This paper presents the experimental research process and results about flue gas purifying of municipal solid wastes (MSW) incineration using in-pipe jet adsorption techniques. MSW incineration was carried out in a fluidized bed test rig, and the flue gas purifying was carried out in an in-pipe jet adsorption test rig. The experimental results are as follows: when the feedstock of activated carbon is 1.6g/Nm(3), the desulfurization efficiency is 83%, the denitrification efficiency is 41%, and the dechlorination efficiency is 27%. The order of purifying effect of the three kinds of adsorbents on acidic gases from MSW incineration is activated carbon>activated bauxite>kaolin. Comparison of adsorption capabilities of the three kinds of adsorbents to heavy metals shows that activated carbon is the best additive to remove Cd, Pb and Cu, kaolin is inferior, and activated bauxite is the worst one. However, activated bauxite is the best additive to remove Hg, and it can remove Cd effectively. PAHs in fly ash are dominated by three-, four-, and five-ringed PAHs, and PAHs in the flue gas mainly include three- and four-ringed PAHs. When the injected quantity of additive is constant, the order of cleaning effect on PAHs is kaolin>activated carbon>activated bauxite. These three kinds of adsorbents have different purifying effects on acidic gases, heavy metals and PAHs in the flue gas from MSW incineration. In general, activated carbon has a better adsorption capability